2014
DOI: 10.3109/14767058.2013.871630
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol effectiveness, safety and blood level monitoring during patent ductus arteriosus closure: a case series

Abstract: Paracetamol was reported to be effective for patent ductus arteriosus (PDA) closure. We present a case series of PDA closure by paracetamol in seven premature infants. During the treatment, paracetamol blood levels did not exceed the recommended levels for analgesia and hyperthermia in six tested infants. None of the patients demonstrated significant disturbances of liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 8 publications
0
36
0
1
Order By: Relevance
“…A transient increase in aspartate and alanine aminotransferases or γ-glutamyl transpeptidase was reported only in six patients enrolled in three of the 14 uncontrolled studies 12 16 20…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A transient increase in aspartate and alanine aminotransferases or γ-glutamyl transpeptidase was reported only in six patients enrolled in three of the 14 uncontrolled studies 12 16 20…”
Section: Resultsmentioning
confidence: 99%
“…This effect could be attributable to the ibuprofen albumin binding with consequent bilirubin displacement 34. A transient increase in aspartate and alanine aminotransferases or γ-glutamyl transpeptidase, without long-term consequences on liver function, has been reported in a small number of neonates receiving paracetamol 12 16 20. These events were observed only in patients receiving high doses of the drug.…”
Section: Discussionmentioning
confidence: 98%
“…Acetaminophen can be given orally, at the same dosage and interval, with similar reported efficacy as the intravenous route. (49) Kessel et al (52) showed that paracetamol levels in infants of age 26 to 30 weeks treated with 15 mg/kg per day orally remained mostly within the recommended range of 10 to 20 mg/mL for analgesia before the fifth and ninth doses, with only 2 of 8 patients exceeding the desired range before the ninth dose.…”
Section: Pharmacologymentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] For case series using intravenous paracetamol, the proportion of successful PDA closure was between 75 and 100%.12-15 Our design was similar, but we had a larger sample size compared to previous case series. The proportion of successful PDA closure was lower at 65.5%, than in the four previous case series.…”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol acts as a peroxidase inhibitor in prostaglandin synthesis. 4 In previous case series involving a limited number of subjects, both oral [5][6][7][8][9][10][11][12] and intravenous preparation [12][13][14][15] of paracetamol showed satisfactory results for PDA closure, with no liver toxicity. Moreover, two randomized, double-blind, control trials showed that oral paracetamol was better than oral ibuprofen.…”
mentioning
confidence: 87%